MANAGEMENT EDUCATION OF THE FUTURE CITY POST COVID-19 GARDEN INFRASTRUCTURE TOUGHESS HUMAN RESOURCES EDUCATED AND HEALTHY (URBAN STUDIES) - Zulkifli Amin; Elfrianto Elfrianto; Bahdin Nur Tanjung (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This study was conducted to answer the challenges of future city management after co-19 how we deal with existing challenges, such as reviving urban parks, as a necessity to turn on good and tough and educated human resources. Of course, the government should not be absent with the existence of a new idea about the concept of urban parks in anticipation of increased pollution and so forth. Understanding about this management should not be ignored continuously because without the existence of good management.Theauthor'sresearch method uses theSystemof Literature Review(SLR) Method, which brings together a variety ofsources of information from journals, books and other articles. To improve theplaybacksource that will begeneratedby theplayerlater.Then, whenthe sourceshave beencollected.